Effect of animal mixing as a stressor on biomarkers of autophagy and oxidative stress during pig muscle maturation. (8th April 2015) - Rubio-González, A.; Potes, Y.; Illán-Rodríguez, D.; Vega-Naredo, I.; Sierra, V.; Caballero, B.; Fàbrega, E.; Velarde, A.; Dalmau, A.; Oliván, M.; Coto-Montes, A.
<x content-type="archive" xml:space="preserve">Abstract</x> The objective of this work was to study the postmortem evolution of potential biomarkers of autophagy (Beclin 1, LC3-II/LC3-I ratio) and oxidative stress (total antioxidant activity, TAA; superoxide dismutase activity, SOD and catalase activity, CAT) in the Longissimus dorsi muscle of entire male ((Large White×Landrace)×Duroc) pigs subjected to different management treatments that may promote stress, such as mixing unfamiliar animals at the farm and/or during transport and lairage before slaughter. During the rearing period at the farm, five animals were never mixed after the initial formation of the experimental groups (unmixed group at the farm, UF), whereas 10 animals were subjected to a common routine of being mixed with unfamiliar animals (mixed group at the farm, MF). Furthermore, two different treatments were used during the transport and lairage before slaughter: 10 pigs were not mixed (unmixed group during transport and lairage, UTL), whereas five pigs were mixed with unfamiliar animals on the lorry and during lairage (mixed group during transport and lairage, MTL). These mixing treatments were then combined into three pre-slaughter treatments – namely, UF-UTL, MF-UTL and MF-MTL. The results show that MF-UTL and MF-MTL increased significantly the muscle antioxidant defense (TAA, SOD and CAT) at short postmortem times (4 and 8 h; P<0.001), followed by an earlier depletion of the antioxidant activity at 24 h postmortem (P<0.05). We also found that mixing unfamiliar animals, both at the farm and during transport and lairage, triggers postmortem muscle autophagy, which showed an earlier activation (higher expression of Beclin 1 and LC3-II/LC3-I ratio at 4 h postmortem followed by a decreasing pattern of this ratio along first 24 h postmortem) in the muscle tissues of animals from the MF-UTL and MF-MTL groups, as an adaptive strategy of the muscle cells for counteracting induced stress. From these results, we propose that monitoring the evolution of the main biomarkers of autophagy (Beclin 1, LC3-II/LC3-I ratio) and muscle antioxidant defense (TAA, SOD, CAT) in the muscle tissue within the first 24 h postmortem may help the detection of animal stress and its potential effect on the postmortem muscle metabolism.